The Impact of Color Harmony on Visual Perception in Still Life Painting - Tolibova Umida Davlat qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
ANNOTATION: This article explores the impact of color harmony on visual perception in still life painting. It examines how color combinations, contrasts, and harmonies influence the viewer’s attention, mood, and aesthetic experience. The study also highlights pedagogical approaches for teaching students to understand and apply color principles effectively in their artworks, drawing on Shovdirov S.A.’s research in visual arts education.